Forwarder agent as a important element in the supply chain - Długołęcka, Karolina; Simiński, Przemysław (Management and Administration Journal, 2023)
The operation of companies in economic reality is a constant attempt at looking for a balance of costs and revenues. Among the activities of logistics, one of the key roles is played by transportation. The article analyzes the potential benefits from monitoring systems. By analyzing the individual elements of the transport process chain, were decomposed. This allowed for identification as the roles fully forwarder, which is the main aim of the article.